2013
DOI: 10.1016/j.neuro.2012.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Manganese inhibits ATP-induced calcium entry through the transient receptor potential channel TRPC3 in astrocytes

Abstract: Chronic exposure to elevated levels of manganese (Mn2+) causes neuronal injury and inflammatory activation of glia. Astrocytes selectively accumulate Mn2+, which inhibits mitochondrial respiration and increases production of reactive oxygen species. We previously reported that sub-acute exposure to low micromolar levels of Mn2+ in primary astrocytes inhibited ATP-induced calcium (Ca2+) signaling, associated with decreased levels of endoplasmic reticulum Ca2+ and increased mitochondrial Ca2+ loads. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…This receptor is inhibited by toxicants such as polybrominated diphenyl ethers (PBDE's) and non-coplanar polychlorinated biphenyl compounds (PCB's), which alter Ca 2+ homeostasis in neural cells [33], [34]. Although MPP + is non-coplanar [35] and could therefore potentially react with RyR, the rapid kinetics of the inhibitory effect with MPP + and 6-OHDA more strongly suggest that they function as channel blockers at the plasma membrane, as demonstrated in recent studies with the divalent metal, Mn 2+ , which reversibly inhibited OAG-induced Ca 2+ transients in astrocytes by competitively decreasing Ca 2+ influx through TRPC3 [21]. The electrophysiological data in the present studies also suggests that MPP + and, to a lesser extent 6-OHDA, acutely decreases ATP-dependent Ca 2+ transients in astrocytes by partly by inhibiting the channel activity of TRPC3.…”
Section: Discussionmentioning
confidence: 96%
“…This receptor is inhibited by toxicants such as polybrominated diphenyl ethers (PBDE's) and non-coplanar polychlorinated biphenyl compounds (PCB's), which alter Ca 2+ homeostasis in neural cells [33], [34]. Although MPP + is non-coplanar [35] and could therefore potentially react with RyR, the rapid kinetics of the inhibitory effect with MPP + and 6-OHDA more strongly suggest that they function as channel blockers at the plasma membrane, as demonstrated in recent studies with the divalent metal, Mn 2+ , which reversibly inhibited OAG-induced Ca 2+ transients in astrocytes by competitively decreasing Ca 2+ influx through TRPC3 [21]. The electrophysiological data in the present studies also suggests that MPP + and, to a lesser extent 6-OHDA, acutely decreases ATP-dependent Ca 2+ transients in astrocytes by partly by inhibiting the channel activity of TRPC3.…”
Section: Discussionmentioning
confidence: 96%
“…These proteins are localized on cell membranes and are able to form a membrane pore to take up divalent Mn from the extracellular matrix. Moreover, Mn may block transient receptor potential channel (TRPC3), a receptor-operated plasma membrane channel of astrocytes that responds to ATP-induced Ca signaling, thus decreasing purinergic signaling [51]. …”
Section: Main Textmentioning
confidence: 99%
“…This intercommunication between astrocytes is dynamic and is influenced by the extent of and frequency of neurotransmitter release which is important in the modulation of synapses in both learning and memory (Perea et al 2009). It was recently reported that Mn disrupts ATP-dependent Ca 2+ signaling in astrocytes by inhibiting entry of Ca 2+ through the plasma membrane subsequent to activation of P2Y purinergic receptors (Streifel et al 2013), suggesting that Ca 2+ -dependent homeostatic processes in astrocytes could be an important target of Mn that likely impacts neuronal physiology.…”
Section: Manganese and Astrocytesmentioning
confidence: 99%
“…Mn can disrupt ATP-induced Ca 2+ signaling and intercellular Ca 2+ waves in astrocytes (Streifel et al 2012), which could be detrimental to neuronal trophic support, rendering affected brain regions both focally hypoxic and with insufficient metabolic support. In this regard, even low levels of Mn 2+ can disrupt ATP-dependent calcium signaling in astrocytes, in part through inhibition of TRPC3 cation channels, which could alter the regulation of cerebral blood flow and therefore negatively impact neuronal homeostasis (Streifel et al 2013). Inhibition of ATP-dependent calcium signaling in primary astrocytes has also been described for the cationic neurotoxicants, 1-methyl-4-phenylpyridinium (MPP + ), and 6-hydroxydopamine, suggesting that disruption of homeostatic calcium signaling in astrocytes may be a common mechanism of injury for structurally diverse compounds affecting dopaminergic brain regions (Streifel et al 2014).…”
Section: Manganese and Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation